PERANAN KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI TIPE MADYA PABEAN BELAWAN DALAM PENANGGULANGAN PENYELUNDUPAN EKSPOR SATWA LIAR YANG DILINDUNGI (Studi Pada KPPBC TMP Belawan) - Prakoso, Bayu; Arifin, syamsul; Mubarak, Ridho (Jurnal Ilmiah Penegakan Hukum, 2016)
The Government and the Directorate General of Customs and Excise have basically tried to eradicate the crime of smuggling, especially the smuggling of exports of wild animals that are protected through customs and excise legislation and customs and excise officials as acting or executing duties of customs and excise legislation, but the effort has not yet reaped maximum results because every year the crime of smuggling of protected wildlife exports is increasing. The results of the research and discussion explain how the implementation of customs regulations by the Customs and Excise Supervision and Service Office of Belawan Middle Customs Type in the prevention of smuggling of protected wildlife exports is carried out thoroughly against Law No.17 of 2006 concerning amendment of Law No.10 of 1995 concerning Customs and Director General Regulation Number: Per-32 / BC / 2014 concerning Customs Procedures in the Export Sector.